Pengembangan Pusat Informasi dan Promosi Untuk Meningkatkan Daya Tarik Wisatawan Pada Masa Pandemi Covid-19 di Desa Tanjung Luar, Lombok - Ahmad Abdan Syukron; Baiq Dian Arianingsih; Bq. Dea Gustina Wandari; Duha Hardiyanti Awalia; Juni Kartini; Lalu Adian Gifari; Moh. Ridho Imam Alfarizi; Rizky Jasahuldia; Rostika Rostika; Siti Nurhaslinda; Saprizal Hadisaputra (Pascasarjana Universitas Mataram, 2021)
This community service aims to improve the tourism village through the creation of information boards and the development of supporting systems and marketing in Tanjung Luar Village, East Lombok Regency. This community service activity was held for forty-five days. This devotion adopts qualitative research methods, with data collection techniques conducted by observation, documentation and interviews. The results showed that community service in the creation of information boards and the development of supporting systems and marketing were able to build the spirit of the community to continue to participate in the development activities of tourist villages. By utilizing institutional networks, the strength of the younger generation, the support of the village government, and social media, the community managed to bring about new tourist attractions, improve accommodation facilities, and better tourism management